Modifikasi Algoritma Kriptografi Klasik dengan Implementasi Deterministic Finite Automata melalui Partisi Pesan Asli berdasarkan Kriteria Pesan Bagian - Angga Wijaya (Journal of Science and Applicative Technology, 2020)
Classical cryptography is study of securing a secret message (plaintext) into a hidden message (ciphertext) which in the process changes each character. The process of converting plaintext into ciphertext is called encryption, the reverse process is called decryption. There is monoalphabetic algorithm, which changes each plaintext letter paired wisely with one particular letter in the ciphertext. The weakness of this algorithm is that the encryption rules can be guessed by analysing the frequency of occurrence of letters. Meanwhile, in polyalphabetic cipher, an algorithm that allows the same letter to be encrypted into different letters. One of them is the Vigenere cipher, which uses keywords that can be repeated to add to the plaintext in the computation of integer modulo. However, this algorithm can be solved using the Kasiski method, because pattern of repeating keywords. In this research, a Deterministic Finite Automata computation model is applied to partition messages before being processed with keywords. Partitions that are formed based on the criteria of message parts ending by the letter E, as letters that often appear in English text. This can increase the security of classical cryptographic algorithms, because they cannot be attacked by frequency analysis or Kasiski methods.